The atlas of shipwrecks & treasure : the history, location, and treasures of ships lost at sea - Pickford, Nigel (Boston : Distributed by Houghton Mifflin, 1994)
A guide to ships lost at sea and the treasures they have yielded, with maps that plot the sites of over 1,400 wrecks around the world.
Includes bibliographical references (p. 195) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
Adult
Keywords: Shipwrecks -- Maps; Treasure troves -- Maps; Buried treasure; Shipwrecks